Anion exchange membrane as well as preparation method and application thereof

By copolymerizing the thienyl backbone monomer with the trifluoroalkyl compound branched monomer, the problem of difficulty in taking into account both flexibility and alkali resistance while improving the conductivity of the anion exchange membrane is solved, and a high-performance anion exchange membrane is achieved.

CN119775540AActive Publication Date: 2025-04-08TIANJIN FEYNMAN POWER TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510289322.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-08
Estimated Expiration
2045-03-12

AI Technical Summary

Technical Problem

While improving the conductivity, existing anion exchange membranes are difficult to take into account both flexibility and alkali resistance and stability, resulting in a degradation of performance in high temperature and alkaline environments.

Method used

The thienyl backbone monomer is used to copolymerize with trifluoroalkyl compound branched monomers to improve the gas and water diffusion properties of the material through sulfur-sulfur interaction, and to accurately control the structural arrangement of thienyl groups and aromatic groups to improve mechanical properties and ionic conductivity.

Benefits of technology

It achieves the improvement of the flexibility and alkali resistance of the film while improving the conductivity, enhances the mechanical properties and ion conductivity of the anion exchange membrane, and is suitable for applications in high temperature and alkaline environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775540A_ABST
    Figure CN119775540A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to an anion exchange membrane and a preparation method and application thereof, and the anion exchange membrane is formed by an ion exchange polymer formed by copolymerization of a thienyl main chain monomer and a trifluoroalkyl compound branched chain monomer, the ratio of thienyl to phenyl in the main chain monomer is fixed; through precise doping copolymerization of thiophene groups, sulfur-sulfur interaction is introduced into a main chain skeleton, gas and water diffusion performance of the material is further changed, main chain flexibility can be improved, conductivity can be improved, the polymer is applied to an anion exchange membrane, comprehensive adjustment of mechanical performance and ionic conduction performance is achieved, and the polymer has a wide application prospect. The main chain of the obtained polymer does not contain ether bonds, the alkali-resistant stability of the anion exchange membrane can be improved due to the structural characteristic of unsaturated bonds, and the method is suitable for recycling industrial wastewater containing eosin B (EB) and reactive red X-3B dyes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to an anion exchange membrane and a preparation method and application thereof. Background Art

[0002] Anion exchange membrane electrolyzer (AEME) is an emerging technology that has many potential advantages in terms of cost and large-scale application compared to proton exchange membrane electrolyzer (PEME) technology. AEME is usually composed of bipolar plates and membrane electrode packaging, among which the membrane electrode assembly (MEA) is the site of electrochemical reaction and is the key component that determines the performance of the electrolyzer. It is usually composed of anion exchange membrane (AEM), ionomer, anode, cathode catalyst layer, and porous layer. AEM plays a vital role in the overall performance and durability of the electrolyzer.

[0003] Anion exchange membranes are made of anion exchange resins by casting, scraping, etc. Existing anion polymers can be divided into the following categories according to their skeleton structure: polyphenylene ethers, polysulfones, polyetheretherketones, polystyrenes, polyethylene rigid skeletons, Trogol base polymers, poly(bis)biphenyl and trifluoromethyl ketone copolymers, polyaryl piperidines, etc. Among them, the first three categories are easy to degrade in alkaline environments because of the unsaturated bonds or oxygen hetero bonds in the main chain skeleton, and the material stability is poor; the conductivity performance of the 4th, 5th, and 6th polyethylene-derived skeletons is poor, and the solubility of the products is reduced after the molecular weight is increased, and the processability into membranes is correspondingly poor; the last two types of polymer skeletons are two materials developed recently.

[0004] The conductivity of anion exchange membranes is mainly determined by the transport properties of the ionic groups (head-groups) on the side chain groups. The polymer skeleton determines the mechanical properties of the membrane and also greatly affects the gas and water diffusion properties of the membrane.

[0005] Patent CN113801352A provides a method for preparing a cross-linked anion exchange membrane with polyaryl piperidine as the main structure. Using biphenyl and terphenyl monomers as raw materials, a hydroxyalkylation reaction with piperidone occurs under superacid catalysis to obtain polyaryl piperidine, and then the polymer is functionalized with piperidine on the polymer molecular chain using iodomethane as a functionalizing agent. Finally, alkyl dibromide is used as a cross-linking agent to achieve cross-linking at the N atom position. The conductivity of the obtained anion exchange membrane is low, and the conductivity is basically around 100 mS / cm at 80°C, and iodomethane with high toxicity is used.

[0006] CN116856004A discloses a quaternary ammonium polybiphenylene anion exchange membrane for producing hydrogen by electrolysis of water using anion exchange membrane and a preparation method thereof. The main chain of the polybiphenylene is obtained by subjecting biphenyl to a Friedel-Crafts hydroxyalkylation reaction with 7-bromo-1,1,1-trifluoroheptane-2-one and 2,2,2-trifluoroacetophenone; the obtained polybiphenylene is dissolved and reacted with trimethylamine, pyridine and N-methylpiperidine to obtain corresponding ionomers, thereby successfully preparing a quaternary ammonium polybiphenylene anion exchange membrane for producing hydrogen by electrolysis of water having both high ionic conductivity and strong alkali resistance and stability. However, the flexibility of the membrane is relatively poor.

[0007] The skeleton of the current poly(bi)biphenyl and trifluoromethyl ketone copolymer anion exchange membrane materials mainly contains benzene rings. This type of structure is relatively rigid, and the interaction between the main chains is mainly van der Waals force. The interaction between the polymer and the catalyst is also limited to this, and the flexibility of the membrane is relatively poor. At the same time, when this type of material is used as a catalyst layer adhesive, the diffusion of gas and water is greatly affected, resulting in poor conductivity of the anion exchange membrane. Therefore, it is becoming increasingly urgent to provide a material that improves the mechanical properties while changing the ion conductivity of the membrane by adjusting the skeleton structure of the polymer. Summary of the invention

[0008] In order to solve the problem that the conductivity and flexibility of existing compounds cannot be taken into account at the same time, the present invention provides an anion exchange membrane and a preparation method and application thereof.

[0009] An anion exchange membrane is formed by copolymerizing an ion exchange polymer of a thiophene main chain monomer and a trifluoroalkyl compound side chain monomer, and the structure of the ion exchange polymer is: ; Wherein, x is an integer of 1-5, y is an integer of 1-5, z is an integer of 1-5, m is an integer of 1-3, and the ratio of thienyl to phenyl in the main chain monomer is fixed.

[0010] Furthermore, the general structural formula of the main chain monomer is as shown in Formula I or Formula II: ; Wherein, the aromatic group Ar is selected from any one of the following monomers containing a phenyl structure: ; R is selected from any one of the following monomers containing a thiophene group: .

[0011] Furthermore, the aromatic groups Ar on both sides of the thiophene group in the formula I are the same group.

[0012] Furthermore, the aromatic groups Ar on both sides of the thiophene group in the formula I are different groups.

[0013] Furthermore, the thiophene group in the formula II is located at any position of the aromatic group Ar.

[0014] Furthermore, the general formula of the trifluoroalkyl compound branched monomer is CF3CO-(CH2) m -X, wherein X is Cl or Br, and m=1-3.

[0015] Furthermore, a method for preparing an anion exchange membrane is provided, the steps of which are main chain monomer synthesis→polymer formation→polymer ionization→membrane preparation and post-treatment, wherein the ion exchange polymer is prepared by polymerizing the main chain monomer and the branched chain monomer under the action of trifluoromethanesulfonic acid, and the ratio of the main chain monomer to the branched chain monomer is 1:1; The trifluoromethanesulfonic acid needs to be added dropwise at 0-4°C, and the temperature in the system is controlled to be ≤10°C during the addition process.

[0016] Furthermore, the synthesis steps of the main chain monomer of the polymer are: (1) Bromination: A thiophene-based compound and a brominating agent are subjected to a bromination reaction in a molar ratio of 1:(2-4) to obtain a thiophene-based bromide compound, wherein the thiophene-based compound is thiophene, dithiophene or terthiophene, and the brominating agent is NBS; (2) Coupling: The thienyl bromide compound obtained in step (2) and the aromatic compound are doped by coupling reaction at a doping molar ratio of 1:(2-4) to obtain a main chain monomer, wherein the aromatic compound is phenylboronic acid or biphenylboronic acid.

[0017] Furthermore, the polymer ionization process is to ionize the polymer under the action of a quaternary ammonium salt to form an ion exchange polymer, wherein the quaternary ammonium salt is a 30% trimethylamine aqueous solution, and the ratio of the polymer to the quaternary ammonium salt is 1: (2~20); the membrane preparation and post-treatment process is to completely replace the Br- on the membrane with OH- after the ion exchange polymer is made into a finished membrane to obtain the anion exchange membrane.

[0018] The anion exchange membrane of the present invention is suitable for use in equipment for recycling and treating industrial wastewater containing eosin B and reactive red X-3B dyes.

[0019] The advantages of the present invention are: The present invention provides an anion exchange polymer with a main chain doped with a thiophene group copolymer, which introduces sulfur-sulfur interaction between the main chain skeletons, thereby changing the gas and water diffusion properties of the material, and can increase the flexibility of the main chain while improving the conductivity and the tensile properties of the membrane; At the same time, by precisely controlling the amount of thiophene groups and aromatic groups, the obtained anion exchange membrane structure is arranged in an orderly manner, which improves the mechanical properties and ion conductivity of the membrane material. The obtained polymer main chain does not contain ether bonds and unsaturated bonds, which can also improve the alkali resistance and stability of the anion exchange membrane. By controlling the addition amount of the main chain monomer, the raw material utilization rate of the reaction is close to 100%, which saves energy and is environmentally friendly while further realizing the comprehensive adjustment of the mechanical properties and ion conductivity properties of the anion exchange membrane, thereby obtaining an anion exchange membrane with superior performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 is the H NMR spectrum of the intermediate 1 bromodithiophene in Example 1 of the present invention; Figure 2 is the H NMR spectrum of the monomer compound after coupling of dithiophene and aromatic group in Example 1 of the present invention; Figure 3 is the nuclear magnetic hydrogen spectrum of the ion exchange polymer with dithiophene doped in the main chain after ionization in Example 1 of the present invention; Figure 4 is a physical picture of the anion exchange membrane prepared in Example 1 of the present invention; Figure 5 is an adsorption effect diagram of the anion exchange membrane prepared in Example 1 of the present invention; Figure 6 1 is a graph showing the change in adsorption percentage of the anion exchange membrane prepared in Example 1 of the present invention at different temperatures. DETAILED DESCRIPTION

[0021] The following will be combined with the drawings in the embodiments of the invention to clearly and completely describe the technical solutions in the embodiments of the invention. Obviously, the described embodiments are only part of the embodiments of the invention, not all of them. Based on the embodiments in the invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the invention.

[0022] It should be noted that the various installation methods and technical terms mentioned in the invention are technical terms that have long been clearly known in the relevant technical field, so no further explanation is given. In addition, the same reference numerals are used for the same components, but this does not affect and should not constitute an accurate understanding of the technical solution by those skilled in the art.

[0023] Example 1 This example provides an anion exchange membrane, which is formed by an ion exchange polymer with dithiophene doped in the main chain. The preparation process is main chain monomer synthesis → polymer formation → polymer ionization → membrane preparation and post-treatment. The specific steps are as follows: (1) Preparation of main chain doped dithiophene monomers: Step 1 (bromination), the outside of the three-necked flask was covered with tin foil to block light, and under nitrogen protection, 10.00 g of dithiophene and 100 mL of dichloromethane were added to the three-necked flask in sequence, and 23.14 g of NBS was added under stirring, and stirred at room temperature for 5 h, and the plate was monitored; Step 2, spot plate monitoring After the reaction is completed, 50 mL of water is added to the reaction system of step 1 for liquid separation; the aqueous phase is back-extracted with dichloromethane, and the organic phases are combined and dried for solid column chromatography to obtain intermediate 1 (bromodithiophene, H NMR spectrum as shown in Figure 1 shown); Step 3 (coupling), under nitrogen protection, 5.00 g of the intermediate 1 obtained in step 2, 4.14 g of phenylboronic acid and 10V of ultra-dry THF were added to a three-necked flask in sequence, and stirring was maintained. After three times of evacuation, 0.18 g of palladium catalyst (the palladium catalyst in this embodiment is Pd(PPh3)4) and 2 mL of 2M potassium carbonate solution were added to the three-necked flask under nitrogen protection, and the flask was evacuated twice. The temperature was controlled at 50-70°C for 10 h, and the reaction was cooled to room temperature after the reaction was complete after the plate was monitored; Step 4: After cooling to room temperature, pour the reaction system of step 3 into methanol (650 mL 10V). After a yellow solid precipitates, filter out the solid, dissolve it, and perform column chromatography to obtain the main chain monomer product (NMR hydrogen spectrum as shown in Figure 2 shown); (2) Preparation of polymers: Step 5 (copolymerization), under nitrogen protection, add 76.20 mL of dichloromethane to the three-necked flask, add 20.73 g of the side chain monomer (the side chain monomer in this embodiment is 7-bromo-1,1,1-trifluoroheptan-2-one) and 12.21 g of the main chain monomer obtained in step 4 in sequence under stirring, stir at room temperature until the system is completely dissolved, place the three-necked flask in an ice water bath, cool the system to 0-4°C, and add trifluoromethanesulfonic acid dropwise under temperature control. During the addition, the temperature in the system is controlled below 10°C. After the addition of trifluoromethanesulfonic acid is completed, slowly raise the temperature of the reaction system to 25°C and stir at 25°C for 18 hrs; Step 6: slowly pour the reaction system in step 5 into ethanol (650 mL 10V), a yellow fibrous solid is precipitated, filter out the solid, and dry the solid in a vacuum drying oven at 70°C for 24 hours; Step 7, fully grind the solid dried in step 6, wash and filter three times with ethanol (650 mL 10V) until the pH of the final filtrate is 6-7, and dry the solid again to obtain an ion exchange polymer; (3) Polymer ionization (formation of ion exchange polymer): Step 8 (ionization), add THF (100 ml) and the dried ion exchange polymer (10.00 g) obtained in step 7 to a three-necked flask, raise the temperature of the system to 25 °C, stir until the solid is completely dissolved, add a 30% mass fraction of trimethylamine aqueous solution (TMA) (17.33 g, 5.0 eq) to the three-necked flask, add deionized water after 6 hours, and after 22 hours, add the solution in the bottle to a beaker containing 1.5 L of isopropanol, stirring while adding, and the system changes from a liquid to an elastic solid; Step 9: After filtering the elastic solid system obtained in step 8, place it in a vacuum drying oven for drying at a temperature of 80°C and dry it for 24 hours to obtain an ion exchange polymer with an ionized main chain doped with dithiophene (H NMR spectrum as shown in FIG. Figure 3 as shown).

[0024] The main chain monomer structure of doped dithiophene is as follows:

[0025] The structure of the ion exchange polymer with main chain doped with dithiophene after ionization is as follows: ; The reaction equation is: ; (4) Preparation and post-treatment of anion exchange membrane: 1) Take 5 g of the main chain doped dithiophene ion exchange polymer, dissolve it in 20 mL of DMSO, keep magnetic stirring, and heat the temperature to 80 ° C to obtain a mixed solution; 2) pouring the mixed solution obtained in step 1) onto a heating table, and heating and drying at 70° C. to obtain a finished film; 3) Soak the finished membrane obtained in step 2) in 1M KOH aqueous solution for 12 hours to ensure that the Br - Completely replaced by OH - , washed with deionized water to obtain the corresponding anion exchange membrane (the actual picture of the membrane is as shown in Figure 4 as shown).

[0026] Example 2 This example provides an anion exchange membrane, which is formed by an ion exchange polymer doped with thiophene in the main chain. The preparation process is the same as that in Example 1, except that thiophene is used as the reaction raw material in the bromination reaction of this example, and the ratio of thiophene to the bromination reagent is 1:1.5; the palladium catalyst used in the coupling reaction of this example is Pd(dtbpf)Cl2, and the obtained main chain monomer structure is: ; In the polymerization reaction of this embodiment, the ratio of the main chain monomer to the side chain monomer is 1:1.2, and the structure of the obtained ionized main chain doped thiophene ionized polymer is: .

[0027] Example 3 This example provides an anion exchange membrane, which is formed by an ion exchange polymer doped with terthiophene in the main chain. The preparation process is the same as that in Example 1, except that in the bromination reaction in this example, thiophene is used as the reaction raw material, and the ratio of thiophene to the bromination reagent is 1:2.5. The obtained main chain monomer structure is: ; In the polymerization reaction of this embodiment, the ratio of the main chain monomer to the side chain monomer is 1:1.2, and the structure of the obtained ionized main chain doped terthiophene ionized polymer is: .

[0028] Comparative Example 1 Using biphenyl as the main chain monomer and 7-bromo-1,1,1-trifluoroheptan-2-one as the side chain monomer, the anion exchange membrane formed by the ionized polymer whose main chain is not doped with thiophene groups is obtained according to the preparation method of the above-mentioned Example 1. The structure of the ionized polymer whose main chain is not doped with thiophene groups is as follows:

[0029] Test experiment 1: The mechanical properties, tensile properties, water absorption swelling ratio and conductivity of the anion exchange membranes obtained in Examples 1-3 were tested respectively, and the results are shown in Table 1: The membrane needs to be pretreated before testing: the anion exchange membrane to be tested needs to be cut into small pieces of 1cm×4cm, immersed in 1M KOH, and the temperature of the KOH solution is maintained at 80℃ for 24h; after the immersion is completed, it is thoroughly washed three times with deionized water until the conductivity of the last washing solution is less than 3μS / cm, otherwise it is washed with deionized water again until the conductivity of the washing solution is less than 3μS / cm.

[0030] The test methods for water absorption and swelling rate are: Water absorption rate: weigh the dried film and record the mass as m1; then soak the film in deionized water at 25°C for 24 hours, take it out and wipe the surface dry; the mass after weighing is recorded as m2; the water absorption rate is: (m2-m1) / m1×100%; Swelling ratio: It is calculated by measuring the change in membrane length before and after absorbing electrolyte, and the formula is: Swellingratio (%) = (Lw - Ld) / Lw × 100%, where Lw and Ld are the lengths of the membrane in the solution saturated state and dry state, respectively.

[0031] The test methods for mechanical properties are: The film's resistance to tensile deformation is tested in both the transverse and longitudinal directions.

[0032] Tested according to ISO 527-3, GB / T 1040.3, ASTM D882 and other standards.

[0033] Test process: Cut the film into long strips, fix the upper and lower ends on the clamps of the test instrument respectively, keep one end still, and move the other end at a constant speed to stretch the film until it breaks completely.

[0034] Data such as secant modulus and tensile strength at break can be obtained, reflecting the tensile stiffness of the film and the force required when it is stretched to break.

[0035] The test method for conductivity is: 1. Electrode installation: Install two parallel electrodes on both sides of the membrane material. The electrode material should be non-reactive to avoid chemical reaction with the membrane material; 2. Environmental control: Place the membrane material and electrodes in a constant temperature and humidity chamber to ensure the consistency of environmental conditions during the test; 3. Voltage application: Apply a known DC voltage to the membrane material through the electrodes; 4. Current measurement: measure the current passing through the membrane material, using a high-precision ammeter to ensure the accuracy of the data; 5. Conductivity calculation: According to Ohm's law, calculate the conductivity of the membrane material, that is: Conductivity (σ) = current (I) / voltage (V) × area (A) / thickness (d), where A is the cross-sectional area of ​​the membrane material and d is the thickness of the membrane material.

[0036] Table 1 Test results of embodiments and comparative examples

[0037] The above data show that the water absorption test results of the anion exchange membrane prepared based on the thiophene-doped ion exchange polymer in Examples 1-3 of the present invention are all <10%, and the swelling rate test results are <12%, and the two indicators are significantly better than the anion exchange membrane prepared from the non-thiophene-doped polymer in Comparative Example 1. At the same time, the anion exchange membrane prepared by the material of the present invention still maintains a relatively high tensile strength, and the test result of the hydroxide ion conductivity of the anion exchange membrane at 80°C reaches more than 170 mS / cm, indicating that the mechanical properties of the material are maintained after thiophene doping while improving the conductivity, showing excellent ion exchange performance, indicating that the material has extremely high potential application value in the field of anion exchange membrane electrolyzers.

[0038] Test experiment 2: The ion exchange capacity of the anion exchange membranes prepared in Examples 1-3 was measured by acid-base titration, and the specific test method is as follows: First, the anion exchange membranes prepared in Examples 1-3 were cut into slices of appropriate size, washed with deionized water for 15 minutes to remove surface impurities, placed in an oven and dried to constant weight, and weighed and recorded after drying.

[0039] Secondly, the dried membrane samples were immersed in an excess of concentrated HCl solution and stirred at room temperature for 48 h to ensure that the OH in the anion exchange membrane - Completely converted to Cl - , filter the solution and separate the membrane sample.

[0040] Finally, phenolphthalein was used as an acid-base indicator and the HCl solution remaining after filtration was titrated with a standardized NaOH solution. The volume of NaOH solution consumed at the titration endpoint was recorded. The ion exchange capacity was calculated based on the stoichiometric relationship of the acid-base titration.

[0041] The specific calculation formula is as follows:

[0042] Where IEC is the ion exchange capacity (meq / g), C1V1 represents the concentration (mol / L) and volume (V) of concentrated HCl solution, C2V2 represents the concentration (mol / L) and volume (V) of NaOH solution, and m represents the mass (g) of the anion exchange membrane after drying.

[0043] The ion exchange capacities of the three membrane materials prepared in Examples 1-3 obtained by the above method and formula are all between 1.2-1.5 meq / g, which can effectively separate and remove specific anions.

[0044] Test experiment 3: By testing the adsorption capacity of the anion exchange membrane prepared in Example 1, the adsorption capacity of the anion exchange membrane for a specified type of dye in industrial wastewater was obtained. The test method for the adsorption capacity is as follows: First, take eosin B dye (also known as eosin B, purchased from Wuhan Kmik Biopharmaceutical Technology Co., Ltd.) and reactive red X-3B dye (purchased from Nanjing Dolai Biotechnology Co., Ltd.) respectively, add water to prepare a series of dye solutions A and B with different mass concentrations (50 mg / L, 100 mg / L, 150 mg / L, 200 mg / L, 300 mg / L), and use a UV-visible spectrophotometer to measure the absorbance at the maximum absorption wavelength and draw a standard curve.

[0045] Secondly, the film was cut into circular specifications to prepare anion exchange membrane discs, which were washed with deionized water for 15 minutes to remove surface impurities and placed in an oven for drying. The weight after drying was 0.1 g, and then the membranes were placed in 100 mL, 150 mg / L dye solution A and 100 mL, 150 mg / L dye solution B for constant temperature oscillation adsorption. The absorbance was measured at the maximum absorption wavelength with an ultraviolet spectrophotometer, and the dye concentration in the solution was calculated according to the standard working curve. The equilibrium adsorption capacity of the anion exchange membrane was obtained through the mass change of the dye in the dye solution.

[0046] The calculation formula of equilibrium adsorption capacity is as follows:

[0047] Where q is the equilibrium adsorption amount (mg / g); C1 is the initial mass concentration of the dye in the dye solution (mg / L); C2 is the mass concentration of the dye in the dye solution after adsorption reaches equilibrium (mg / L); V is the volume of the solution (L); and m is the mass of the anion exchange membrane after drying (g).

[0048] The changes of adsorption amount under different adsorption time are as follows Figure 5 As shown, it can be concluded that the anion exchange membrane prepared in Example 1 reaches adsorption equilibrium in 120 min in the treatment of wastewater containing eosin B dye or reactive red X-3B dye, the maximum adsorption amount of eosin B is 80 mg / g, and the maximum adsorption amount of reactive red X-3B is 60 mg / g.

[0049] According to this method, the effects of anion exchange membrane on the adsorption performance of eosin B dye and reactive red X-3B at different temperatures were tested. The results are as follows: Figure 6 As shown, it can be seen that the adsorption percentage decreases with the increase of temperature, but it shows a stable trend overall, indicating that in the treatment of dye-containing wastewater, the effect of temperature on the adsorption process is very small and does not affect the change in the adsorption amount, which is conducive to the treatment of dye industrial wastewater at room temperature.

[0050] The above experimental data show that the anion exchange membrane of the present invention has excellent anion conductivity, chemical stability, mechanical properties and solubility, and has adsorption and removal effects on specific ions, and is suitable for use in batteries for sewage treatment in special scenarios.

[0051] For those skilled in the art, the invention is not limited to the details of the above exemplary embodiments, and can be implemented in other specific forms without departing from the spirit or basic characteristics of the invention; therefore, no matter from which point of view, the embodiments should be regarded as exemplary and non-restrictive, and the scope of the invention is defined by the appended claims rather than the above description, so it is intended to include all changes within the meaning and scope of the equivalent elements of the claims. Any reference numerals in the claims should not be regarded as limiting the claims involved.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any minor modifications, equivalent substitutions and improvements made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the technical solution of the present invention.

Claims

1. An anion exchange membrane, characterized in that It is formed by copolymerizing thiophene main chain monomers and trifluoroalkyl compound side chain monomers to form an ion exchange polymer, and the structure of the ion exchange polymer is: ; Wherein, x is an integer of 1-5, y is an integer of 1-5, z is an integer of 1-5, m is an integer of 1-3, and the ratio of thienyl to phenyl in the main chain monomer is fixed.

2. An anion exchange membrane according to claim 1, characterized in that: The general structural formula of the thienyl main chain monomer is shown in Formula I or Formula II: ; Wherein, the aromatic group Ar is selected from any one of the following monomers containing a phenyl structure: ; R is selected from any one of the following monomers containing a thiophene group: 。 3. An anion exchange membrane according to claim 2, characterized in that: The aromatic groups Ar on both sides of the thiophene group in the formula I are the same group.

4. An anion exchange membrane according to claim 2, characterized in that: The aromatic groups Ar on both sides of the thiophene group in the formula I are different groups.

5. An anion exchange membrane according to claim 2, characterized in that: In the formula II, the thiophene group is located at any position of the aromatic group Ar.

6. An anion exchange membrane according to claim 1, characterized in that: The general formula of the trifluoroalkyl compound branched monomer is CF3CO-(CH2) m -X, wherein X is Cl or Br, and m=1-3.

7. A method for preparing an anion exchange membrane according to claim 1, wherein the steps are main chain monomer synthesis → polymer formation → polymer ionization → membrane preparation and post-treatment, characterized in that: The ion exchange polymer is prepared by polymerizing a main chain monomer and a side chain monomer under the action of trifluoromethanesulfonic acid, wherein the ratio of the main chain monomer to the side chain monomer is 1:1; The trifluoromethanesulfonic acid needs to be added dropwise at 0-4°C, and the temperature in the system is controlled to be ≤10°C during the addition process.

8. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The synthesis steps of the main chain monomer are: (1) Bromination: A thiophene-based compound and a brominating agent are subjected to a bromination reaction in a molar ratio of 1:(2-4) to obtain a thiophene-based bromide compound, wherein the thiophene-based compound is thiophene, dithiophene or terthiophene, and the brominating agent is NBS; (2) Coupling: The thienyl bromide compound obtained in step (2) and the aromatic compound are doped by coupling reaction at a doping molar ratio of 1:(2-4) to obtain a main chain monomer, wherein the aromatic compound is phenylboronic acid or biphenylboronic acid.

9. The method for preparing an anion exchange membrane according to claim 7, characterized in that: The polymer ionization process is to ionize the polymer under the action of a quaternary ammonium salt to form an ion exchange polymer, wherein the quaternary ammonium salt is a 30% trimethylamine aqueous solution, and the molar ratio of the polymer to the quaternary ammonium salt is 1: (2-20); the membrane preparation and post-treatment process is to make the ion exchange polymer into a finished membrane and then remove the Br on the membrane. - Completely replaced by OH - , to obtain the anion exchange membrane.

10. An application of the anion exchange membrane according to any one of claims 1 to 6, characterized in that: The anion exchange membrane is suitable for recycling and treating industrial wastewater containing eosin B type and reactive red X-3B type dyes.

Citation Information

Patent Citations

  • Anion exchange membrane, and preparation method and application thereof

    CN113801352A

  • Novel polymers and methods for manufacturing same

    CN107112563A

  • Polymers having stable cationic pendant groups for use as anion exchange membranes

    CN114025957A

  • Preparation process of electrolyte membrane material containing conjugated structure

    CN118852593A

  • Polyaromatic electrolytes for alkaline membrane fuel cells

    US11476485B1

Cited By

  • Side chain type polyaryl anion-exchange membrane, preparation method and application thereof and anion-exchange membrane electrolytic cell

    CN120485868A

  • An anion exchange membrane containing short-chain 6,6-spirocyclic piperidine quaternary ammonium salt units and a preparation method and application thereof

    CN122806318A